A Novel Technique for Vector Control of Single-Phase Induction Motors Based on Rotor Field-Oriented Control - Mohammad Jannati; Sajad Abdollahzadeh Anbaran; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (Institute of Advanced Engineering and Science, 2014)
Due to asymmetrical characteristics of single-phase IMs, conventional vector control methods for three-phase IMs cannot be directly applied to single-phase IMs. This study aims to improve performance of the single-phase IMs drive system. Hence, a novel control approach based on Rotor Field-Oriented control (RFOC) was developed for single-phase IMs. For this purpose, transformation matrices are applied to the machine equations. It is shown by applying these transformation matrices to the unbalanced equations of single-phase IM results in set of balanced equations with backward and forward components. Therefore, by some modifications in the conventional RFOC method for three-phase IM, vector control of single-phase IM can be done. The proposed method demonstrates reasonably good speed and torque responses with satisfactory tracking capability. It is shown the effect of using this supposition is reflected on the motor torque and hence speed oscillations. Due to good tracking capability of proposed drive system, this control technique can be a well-suited candidate for application where precise move of IM in required such as cutting, knurling and deformation processes.